Seismic behaviour and design of irregular and complex civil structures - De Stefano, Mario; Lavan, Oren (Geotechnical, Geological and Earthquake Engineering, 2013)
Structural irregularities are one of the most frequent causes of severe damages in buildings, as evidenced by the numerous earthquakes in recent years. This issue is of particular importance, since real structures are almost all irregular. Furthermore, structural irregularities depend on several factors often very difficult to predict. This book is an essential tool for understanding the problem of structural irregularities and provides the most up-to-date review on this topic, covering the aspects of ground rotations, analysis, design, control and monitoring of irregular structures. It includes 24 contributions from authors of 13 countries, giving a complete and international view of the problem.